Genomics of primary chemoresistance and remission induction failure in paediatric and adult acute myeloid leukaemia. (21st October 2016) - Brown, Fiona C.; Cifani, Paolo; Drill, Esther; He, Jie; Still, Eric; Zhong, Shan; Balasubramanian, Sohail; Pavlick, Dean; Yilmazel, Bahar; Knapp, Kristina M.; Alonzo, Todd A.; Meshinchi, Soheil; et al.
Summary: Cure rates of children and adults with acute myeloid leukaemia (AML) remain unsatisfactory partly due to chemotherapy resistance. We investigated the genetic basis of AML in 107 primary cases by sequencing 670 genes mutated in haematological malignancies. SETBP1, ASXL1 and RELN mutations were significantly associated with primary chemoresistance. We identified genomic alterations not previously described in AML, together with distinct genes that were significantly overexpressed in therapy‐resistant AML. Defined gene mutations were sufficient to explain primary induction failure in only a minority of cases. Thus, additional genetic or molecular mechanisms must cause primary chemoresistance in paediatric and adult AML.